Coping skills of children experiencing loss and grief :|ba descriptive study among chinese children in salvation army, Kuching who experienced loss and grief - Liong,, Siau Wui. (Universiti Malaysia Sarawak (UNIMAS), 2008)
This is a descriptive paper meant to study young children’s grieving stages and their coping skills on loss. The researcher’s intention is to identify the coping skills exhibits by children who have experienced loss of parent(s), the grieving stages gone through by children who have experienced loss of parent(s), and the emotional reactions of children have towards loss of parent(s). There are five (5) informants in this study, aged eleven (11) and twelve (12), with four (4) of them are boy. The material used in this study is the Nader’s Post-Trauma Stress Disorder (PTSD) Coping Questions. Semi-structured interview, unstructured interview, and observations are the methods used in this study to collect data. The obtained data are then analysed through descriptive data analysis.There are three (3) main concepts and seven (7) sub-concepts being identified and discussed in this study, namely the denial stage, coping skills exhibit by the informants –self-talk, keeping busy, and seeking social support, and emotional state of the informants during the interview –denial, emotional numbness, anger, and irritability.